Family of [Ln4Mn8] (Ln = Gd, Tb, Dy, Ho) and Y4Mn8 single-molecule magnets from the use of 2-(pyridine-2-yl)propan-2-ol. (15th November 2018) - Pham, Linh; Abboud, Khalil A.; Wernsdorfer, Wolfgang; Christou, George
Graphical abstract: Heterometallic [Ln III 4 Mn III 8 ] (Ln = lanthanide) clusters, and their [Y III 4 Mn III 8 ] analogue, have been synthesized. The Dy complex is a single-molecule magnet, confirmed by the observation of hysteresis loops in magnetization versus field scans. Abstract: The syntheses, structures and magnetic properties are reported of a new family of [Ln4 Mn8 O8 (O2 CPh)16 (dmhmp)4 ] (Ln = Gd (1 ), Tb (2 ), Dy (3 ), Ho (4 )) complexes obtained from the use in Mn–Ln chemistry of 2-(pyridine-2-yl)propan-2-ol (dmhmpH), a bulkier derivative of 2-(hydroxymethyl)pyridine (hmpH) containing a CMe2 OH arm instead of CH2 OH. Complexes1 –4 were obtained from the reaction of Mn(O2 CPh)2, Ln(NO3 )3, dmhmpH and NEt3 in a 2:1:2:4 molar ratio in MeCN/MeOH (24:2 mL), and the corresponding reaction with Y(NO3 )3 gave [Y4 Mn8 O8 (O2 CPh)16 (dmhmp)4 ] (5 ). The crystal structures of representative complexes1 and5 were solved and they are isostructural, with centrosymmetric structures comprising five metal-containing layers in anABCBA arrangement, withA = Gd(Y), B = Mn2 Gd(Y), andC = Mn4 . Variable-temperature, solid-state dc and ac magnetic susceptibility studies on1 –5 revealed dominant antiferromagnetic interactions between the Mn8 unit and the Ln III ions. The data for5 ostensibly indicated a well-isolated singly-degenerate ground state, but further studies suggested instead that the ground state is an S = 5 state that is near-degenerate with one or more states with S ≤ 4. Frequency-dependent ac in-phase χ ′ M T and out-of-phase χ ″ M signals indicate3 (Dy) to possibly be an SMM, and this was confirmed by observation of hysteresis loops below 1.6 K in magnetization versus dc field scans below 2 K.